Electroacupuncture and Transcutaneous Electrical Nerve Stimulation Induced Sensations in Bell’s Palsy Patients: A Quantitative Current Intensity Analysis - Cui, Han; Yu, Haibo; Huang, Xingxian; Wu, Lixiong; Zhong, Weizheng; Gou, Yanhua; Cao, Xuemei; Liu, Yongfeng; Hong, Yuanyuan; Zhang, Shaoyun; Zhan, Minmin; Li, Guanglin; et al. (Frontiers in Neuroscience, 2021)
Background The intensity of electrical acupoint stimulation such as electroacupuncture (EA) and transcutaneous electrical nerve stimulation (TENS) is regulated by the observation of skin shivering or the participant’s comfort response. However, the specific intensity and spatial scope following EA or TENS stimulation are unclear. Objective This study aimed to test the stimulatory current intensities of lower and upper sensation thresholds in TENS- and EA-based treatment of Bell’s palsy patients. Also, the spatial scope of the stimulation at these current intensities was simulated and measured quantitatively. Methods A total of 19 Bell’s palsy patients were recruited. Six acupoints on the affected side of the face were stimulated by TENS and EA successively at 30-min intervals. During the stimulation, the current intensity was regulated gradually from 0 to 20 mA, and we simultaneously measured the lower (sensory) and upper (tolerability) sensations. After the treatment by TENS and EA, the modified Chinese version of the Massachusetts General Hospital Acupuncture Sensation Scales (C-MMASS) was applied to survey the de-qi sensations during stimulation. Additionally, we analyzed the correlation between current intensities and C-MMASS and comfort scores. Finite element models were established to depict the spatial distribution of electric field gradients at the lower and upper thresholds. Results The mean sensory and tolerability thresholds of TENS were 3.91–4.37 mA and 12.33–16.35 mA, respectively. The median sensory and tolerability thresholds of EA were 0.2 mA and 2.0–3.2 mA, respectively. We found a significant correlation between total C-MMASS scores and the current intensities at the tolerability threshold of TENS. The finite element model showed that the activated depths of TENS and EA at the lower threshold were 3.8 and 7 mm, respectively, whereas those at the upper threshold were both 13.8 mm. The cross-sectional diameter of the activated area during TENS was 2.5–4 times larger than that during EA. Conclusion This pilot study provided a method for exploring the current intensity at which the de-qi sensations can be elicited by TENS or EA. The finite element analysis potentially revealed the spatial scope of the electrical stimulation at a specific current intensity.